Ionogel-based flexible stress and strain sensors. Issue 3 (3rd July 2021) - Zhao, Gengrui; Lv, Bo; Wang, Honggang; Yang, Baoping; Li, Zhenyu; Junfang, Ren; Gui, Gao; Liu, Wenguang; Yang, Shengrong; Li, Linlin
ABSTRACT: Ionogels is a kind of hybrid materials composed of ionic liquids (ILs) and solid polymer network matrix, has been extensively investigated in the most recent decade. Due to the excellent mechanical properties and ionic conductivity, their promising applications in flexible stress and strain sensors have been proposed and explosively developed. In this review, we briefly summarize research progresses on ionogel based flexible stress and strain sensors (IFSSs) from five aspects, including material synthesis, device fabrication, working principles, characteristics and performances, and potential applications. Some outlooks and perspectives are also proposed at the end of review. The review is expected to provide reference and new insights into the research of IFSS. Graphical abstract: uf0001